Role of JAK-STAT signaling pathway in pathogenesis and treatment of primary Sjögren's syndrome - Li, Mucong; Li, Mengtao; Qiao, Lin; Wu, Chanyuan; Xu, Dong; Zhao, Yan; Zeng, Xiaofeng (Chinese medical journal, 2023)
Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease with high prevalence and possible poor prognosis. Though the pathogenesis of pSS has not been fully elucidated, B cell hyperactivity is considered as one of the fundamental abnormalities in pSS patients. It has long been identified that Janus kinases-signal transducer and activator of transcription (JAK-STAT) signaling pathway contributes to rheumatoid arthritis and systemic lupus erythematosus. Recently, increasing numbers of studies have provided evidence that JAK-STAT pathway also has an important role in the pathogenesis of pSS via direct or indirect activation of B cells. Signal transducer and activator of transcription 1 (STAT1), STAT3, and STAT5 activated by various cytokines and ribonucleic acid contribute to pSS development, respectively or synergically. These results reveal the potential application of Janus kinase inhibitors for treatment of pSS, which may fundamentally improve the quality of life and prognosis of patients with pSS.